Community Empowerment Based on Locality Development to Improving Social Welfare Through Pancur Cave Tourism In Jimbaran Village - Ahmad Kharis; Anggih Zuris Tiani; Nteza Fazil (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
This study aims to discuss the stages of community empowerment based on locality development in improving social welfare and the impact of its emergence through Goa Pancur tourism in Jimbaran Village, Kayen District, Pati Regency. Researchers propose two formulations of the problem, namely 1) How are the stages of community empowerment in improving social welfare in Goa Pancur tourism, Jimbaran Village, Kayen District, Pati Regency? 2) What are the economic, social, and environmental impacts of Gua Pancur Tourism Management and Development? This research method is descriptive qualitative with the type of Field Research. Data was acquired from primary sources: interviews with POKDARWIS, the village government, and the Jimbaran Village community. In contrast, secondary data were obtained from village profiles, tourism decree, activity photos, websites, and social media of Gua Pancur. Techniques in data collection are done by interview, observation, and documentation. The results showed 1) stages of community empowerment from before the management of tourism by POKDARWIS until now experiencing significant development this can be seen from the number of visitors to Gua Pancur tourism is increasing every year. 2) the impact of the existence of Gua Pancur tourism is very diverse; the existence of Gua Pancur tourism has an impact on improving the social welfare of the local community; this can be seen from the growing economy of the community from the existence of jobs and more business opportunities.